Sourdough Breads From The Bread Machine : 100 surefire recipes for everyday loaves, artisan breads, baguettes, bagels, rolls, and more - Anderson, Michelle, (Chef) (Beverly : Harvard Common Press, 2022)
"Sourdough Breads from the Bread Machine shows that the easiest way to make extraordinary sourdough loaves, rolls, biscuits, bagels, and more is with your bread machine"--.
Includes index.
new book 2023 winter.
Keywords: Sourdough bread; Cooking (Bread); Automatic bread machines; Cookbooks